Sistem Informasi Bimbingan Belajar Berbasis Web dengan Metode Waterfall - Situmorang, Daud; Fitri, Iskandar; Benrahman, Benrahman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The creation of a web-based information system at the North Jakarta Sunter branch of Kumon tutoring is intended to improve service quality and quality in the implementation of teaching and learning activities. Based on this, this study will develop a web-based information system that includes an interface design, namely the main page, login, subjects, schedule of subjects, and grades. Making this system an effort to optimize service performance to students.
Keywords: Web Design Application; Design and Implementation Application Information Systems